Increased dual-task interference during upper limb movements in stroke exceeding that found in aging – a systematic review and meta-analysis - Lindberg, Påvel G.; AmirShemiraniha, Nadia; Krewer, Carmen; Maier, Marc A.; Hermsdörfer, Joachim (Frontiers in Neurology, 2024)
Objective: To determine whether dual-task interference during upper limb tasks is increased in patients after stroke compared to healthy older subjects beyond that explained by agerelated changes.We conducted a systematic literature search in MEDLINE, CINAHL, Google Scholar and PEDro databases up to October 2023 for studies on upper limb dual-tasks in stroke andor elderly healthy subjects. Eleven upper limb dual-task studies in stroke patients and 11 studies in healthy older subjects were identified and systematically reviewed. A metaanalysis was performed on seven stroke studies and on five studies in healthy older subjects that included a control groups.Results: Most stroke studies investigated proximal arm movements with kinematic measures, but few studies evaluated manual dexterity. In contrast, studies in healthy older subjects used more distal (finger tapping) tasks. The meta-analysis showed that stroke patients had on average a 19% (CI95%=1.0-37.3) increase in dual-task interference compared to age-matched healthy controls (Z=2.06, P=0.04). Older healthy subjects showed greater dual-task interference compared to younger subjects (19% greater, Z=2.98, P=0.003).Conclusions: Meta-analysis revealed an increase in dual-task interference during upper limb movements in stroke patients, exceeding age-related changes, supporting . The results support the presence of subclinical impairments in divided attention post-stroke that may impede motor recovery.